FORMING VALEOLOGICAL CULTURE IN STUDENTS THROUGH FOLK GAMES - Hakimova Gulshan Abduxalil qizi (American Journals, 2025)
This article provides detailed information on the system of forming valeological culture in female students through the use of folk games.
Keywords: Folk games, active games, female students, physical culture, formation, technology, forms, methods, means, education, upbringing, health promotion.